The Impact of Government Expenditure Budget on Economic Growth In The Case Of Ethiopia - Samuel Atsibha Gebreyesus (Journal of Economic and Social Development (Varaždin), 2022)
The paper examines the impact of government expenditures on economic growth in Ethiopia based on annual time series data from 1991 to 2016, gathered from the Ethiopian Ministry of Finance and World Bank databases. Economic growth depends on capital and recurrent expenditure, agriculture, industry, trade, foreign direct investment, services, and inflation. The regression model between the variables Durbin-Watson and VIF Test for autocorrelation and multicollinearity was the instrument of analysis. The findings show that the dependent variable of economic growth has a positive and significant relationship with the predictors of trade, capital expenditure, and services. The beta coefficient is highly positive for capital expenditure, trade, and the service sector, implying that the higher the investment in services and trade, as well as an increase in capital expenditure, the greater the economic growth. The government should increase its efforts to guarantee that resources are appropriately managed and invested in producing areas to support economic growth.